Nitrogen fixing efficiency and physiological characteristics of Azospirillum isolates from the paddy fields of North Bengal (Jahangirnagar University Journal of Biological Sciences, 2016)
The microbial activity of ten selected Azospirillum isolates was measured in terms of the amount of CO2 evolved by the isolates after incubation for 5 days which ranged from 6.88 to19.25 mg. Nitrogen fixing efficiency all of the isolates was determined by microkjeldhal method and the nitrogen fixing efficiency ranged from 10.03 to 13.11 mg N/g substrate. The growth of Azospirillum isolates was significant affected by different physiological factors such as pH, temperature and salinity. Most of the isolates showed optimum growth at pH 6.8, temperature 37°C and in the absence of NaCl. Azospirillum has the potential to be used as a substitute and or supplement of N-fertilizers. Further research is needed to estimate N-supplement potentials of biological nitrogen fixation (BNF) systems at the farm level.Jahangirnagar University J. Biol. Sci. 3(1): 47-53, 2014 (June)